Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ajhb.23074
|View full text |Cite
|
Sign up to set email alerts
|

Separating the Bruce and Trivers‐Willard effects in theory and in human data

Abstract: Attempts to identify mechanisms by which reproductive suppression affects fetal loss and characteristics of human birth cohorts should consider the Bruce Effect as an alternative to the Trivers-Willard Effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
(53 reference statements)
2
14
0
Order By: Relevance
“…Additionally, several studies in humans have generalized the term "Bruce effect" to refer to spontaneous abortion in response to a range of stressful environments that may threaten offspring survival. 19,20,104 While severe stress is undoubtedly an important factor in human fertility and reproduction, we discourage the use of the term "Bruce effect" unless pregnancy loss can be attributed to exposure to a nonsire male.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies in humans have generalized the term "Bruce effect" to refer to spontaneous abortion in response to a range of stressful environments that may threaten offspring survival. 19,20,104 While severe stress is undoubtedly an important factor in human fertility and reproduction, we discourage the use of the term "Bruce effect" unless pregnancy loss can be attributed to exposure to a nonsire male.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that evidence of fetal loss induced by threats to young conspecifics may appear in humans (Catalano, Saxton, Gemmill, & Hartig, ). Consistent with this suggestion, research finds indicators of adaptive fetal loss (eg, lower ratio of males to females at birth; lower ratio of live born male twins to male singletons) in historic and contemporary human populations that witnessed unusually frequent death among children (Catalano et al, , ; Saxton, Gemmill, & Catalano, ).…”
Section: Introductionmentioning
confidence: 86%
“…Following earlier research into reproductive suppression in humans (Catalano et al, ), we specified our independent variable as the odds of death among Swedes aged 1 to 9. Theoretical and empirical literature attributes reproductive suppression, at least in part, to signals of death among conspecifics between their birth and the onset of reproductive capacity (Bartoš et al, ; Labov, ; Palombit, ; Roberts et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations